THE DEVELOPMENT OF THE LITERACY OF QUR'á¾¹NIC INTERPRETATIONS IN SUDAN: CRITICAL STUDY OF THE AL-TAFSÄªR AL-TAUá¸¤ÄªDÄª - Hasan, Moh Abdul Kholiq (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
This article aims to critically explain the method of al-TafsÄ«r al-Tauá¸¥Ä«dÄ« by á¸¤asan al-TurÄbÄ« and its position amongst other thematic commentary theories. This study is a descriptive qualitative study by employing content analysis theory. The results indicate the trend of al-TafsÄ«r al-Tauá¸¥Ä«dÄ« in two meanings. The first is as a commentary paradigm which leans on the unity of man and the universe in the message of the God's revelation. The second is as the form of thematic commentary of al-Waá¸¥dah al-Mauá¸Å«â€˜iyyah model. Therefore, this commentary is more appropriately categorized into al-TafsÄ«r al-Muá¹£hafÄ« bi al-Waá¸¥dah al-Mauá¸Å«'iyyah. It has three systematic explanation in each surah including KhulÄá¹£ah Hady al-SÅ«rah, TartÄ«l al-Ma'Äni, and UmÅ«m al-ma'Äni. Al-TurÄbÄ«'s ability to unite various related elements in his commentary is not only between verses or surahs but also between human life and all its activities with the universe in a bond of al-Qur'an guidance which is core to monotheism. This is the advantage it has and is a new method in commentary literacy in Sudan. In fact, the method of al-TafsÄ«r al-Tauá¸¥Ä«dÄ« generally becomes a framework for the whole civilization project of al-TurÄbÄ«. However, there are some critics towards his commentary regarding rationality and rejection of several authentic hadiths which seem to leave riwÄyah in the commentary of the Qur'an.